Cixutumumab reveals a critical role for IGF-1 in adipose and hepatic tissue remodelling during the development of diet-induced obesity. (31st December 2022) - Imrie, Helen; Viswambharan, Hema; Haywood, Natalie J; Bridge, Katherine I; Yuldasheva, Nadira Y; Galloway, Stacey; Simmons, Katie J; Cubbon, Richard M; Sukumar, Piruthivi; Watt, Nicole T; Lichtenstein, Laeticia; Wyatt, Judy I; et al.
ABSTRACT: High fat diet (HFD)-induced obesity leads to perturbation in the storage function of white adipose tissue (WAT) resulting in deposition of lipids in tissues ill-equipped to deal with this challenge. The role of insulin like growth factor-1 (IGF-1) in the systemic and organ-specific responses to HFD is unclear. Using cixutumumab, a monoclonal antibody that internalizes and degrades cell surface IGF-1 receptors (IGF-1 R), leaving insulin receptor expression unchanged we aimed to establish the role of IGF-1 R in the response to a HFD. Mice treated with cixutumumab fed standard chow developed mild hyperinsulinemia with no change in WAT. When challenged by HFD mice treated with cixutumumab had reduced weight gain, reduced WAT expansion, and reduced hepatic lipid vacuole formation. In HFD-fed mice, cixutumumab led to reduced levels of genes encoding proteins important in fatty acid metabolism in WAT and liver. Cixutumumab protected against blunting of insulin-stimulated phosphorylation of Akt in liver of HFD fed mice. These data reveal an important role for IGF-1 R in the WAT and hepatic response to short-term nutrient excess. IGF-1 R inhibition during HFD leads to a lipodystrophic phenotype with a failure of WAT lipid storage and protection from HFD-induced hepatic insulin resistance.